Understanding architectural design and style as forms of communication : Chinese architecture in the Pearl River Delta - REVILLOSA, VERMON BRYAN (Archīum Ateneo, 2017)
Two extremely different styles identify the modern Chinese architecture. Identity of modern Chinese architecture faces great challenges in terms of the contrast of conventional and contemporary design styles that may lead to a fall to either adaptation to modernity or awareness and preservation of culture and tradition. The research was supported by several related literatures of both architectural and communication disciplines. Focus ethnographic research was also accomplished. The correlation of physical and theoretical foundation with practical application generated richer comprehension of the reality implied and communicated by Chinese architecture. Findings suggested that the socially constructed Chinese identity is encapsulated by Western exterior design, which adhered to the studied theoretical framework particularly through the phenomenological tradition. Results showed that architectural structures have the capacity to be converted to a coded language that can be communicative. Coded identifiers were recognized as essential to Chinese culture; which reflect strong cultural identity.